Grassroots innovation and social innovation in perspective - Maldonado-Mariscal, Karina (Frontiers in Sociology, 2023)
This article provides a comprehensive review of social innovation and grassroots innovation over the last five years, offering a detailed analysis of both concepts. This study explores the integration of grassroots innovation and social innovation based on an extensive literature review. It examines five dimensions within the literature: key fields, disciplines, actors, geographical areas and theoretical frameworks. Despite significant research in recent decades, there is a notable gap of literature devoted to grassroots innovation and its position within discourse of social innovation. This paper explores the differences and similarities between the concepts of social innovation and grassroots innovation in order to better understand the use of both concepts, the cases in which they are used and possible complementarities. The main findings of the literature on combining the concepts of social innovation and grassroots innovation focus on social enterprises, while research on grassroots innovation as a stand-alone concept focuses on community-led initiatives, civil society organisations, cooperatives and local leaders. Geographically, India plays a very important role in grassroots and social innovation research, followed by Brazil and Spain. In terms of theoretical approach, the combination of social innovation and grassroots innovation has a strong sociological focus, emphasising theories of social practice, collective action, solidarity and community. In contrast, the theoretical frameworks of grassroots innovation are more anchored in power relations and socio-technical transitions, including, for example, resistance to innovation. Grassroots innovation offers practical insights into understanding innovation through the lenses of grassroots and community-based social change. Similarly, social innovation can contribute to the debate on grassroots innovations by understanding not only the agency of actors, but also the innovation ecosystem, actors and types of innovation. Further empirical research on the understanding and application of both concepts in the global North and South in academic discourse offers great potential, therefore potential research questions have been raised here for further investigation.